(3CSeGA TjhN eGdcs - (3GdMGaX eMeO Hf ESeGYjd Hf Ndahf GdGROj, CHh YHO Gddg,J (B636 (3g` s
(3ChdgG (B:s
(3CeG HYO QMefG Gddg hEjGce aEfi PcQJ ai cJGHi gPG GSeGA TjhN eGdc Hf CSi s
(3BNQgG (B:s
(3Cf YGFTI Ce GdeDefjf cGfJ ai MUf Hfi MGQKI jhe GdNfOb hcGf ef Cbhi MUhf GdeOjfI hPcQ GdMOjK Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B36s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B15 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdESchQjGd s
Keywords: (3GdJGQjNs